1027 Effect of Clonazepam on Obstructive Sleep Apnea Coexisting with REM Behavior Disorder: A Case Report. (12th April 2019) - Koothirezhi, Rupa; Scuteri, Brian; Roberts, Edmond; Kilaikode, Sasikumar; Luther, Euil; Liendo, Cesar; Chernyshev, Oleg
Abstract: Introduction: Rapid eye movement behavior disorder (RBD) is a parasomnia characterized by loss of muscle atonia during REM sleep, resulting in excess motor activity and dream enactment. These behaviors may lead to interrupted sleep and injury to the person or their bed partner. Obstructive sleep apnea can coexist with RBD and the treatment of one may affect the course of other condition. We report a case of RBD and the effect of Clonazepam treatment on the severity of concomitant OSA. Report of case: Sixty six year old female without any significant past medical problems presented with abnormal behavior during sleep including screaming and attempt to ambulate, sometimes resulting in injury. She also had snoring and daytime fatigue. She did not have symptoms of cataplexy and she was not on SSRI. Detailed evaluation was negative for underlying neurological/psychiatric disorder. Her Epworth sleep scale (ESS) score was 2. Overnight polysomnography was significant for RBD and OSA (AHI 5.5/hour). She was initiated on Clonazepam & Melatonin for RBD and CPAP for OSA. Over next few years, she reported improvement in behavioral symptoms during sleep, but developed worsening of daytime sleepiness (ESS score 7). Repeat polysomnography showed AHI of 16/hour. There was significant improvement in observed REM behavioral abnormalities compared to previous study. Regarding OSA, she developed CPAP intolerance, eventually requiring BiPAP as indicated by titration study with subsequent improvement in symptoms. Conclusion: There is paucity of data on the complex interplay between RBD and OSA. Clonazepam is commonly used to treat RBD, but the mechanism of action is unclear. Clonazepam may possibly be associated with worsening of OSA, as observed in our patient and few previously reported cases. Knowledge on the underlying cause of this effect is limited. Our patient was also on Melatonin, but previous reports showed Melatonin might be associated with improvement in OSA. Our case shows the need for watching for onset or worsening of OSA symptoms in patients with RBD on Clonazepam. This observation also indicates the necessity of further research in this field. Support: none